Tribology Engineering : Selected, Peer Reviewed Papers from the International Conference on Engineering Tribology Technology 2014 (ICETT 2014), November 21-23, 2014, Nantou, Taiwan - Hwang, Yunn-Lin; Horng, Jeng-Haur; Wei, Chin-Chung (Trans Tech Publishers, 2015)
Collection of selected, peer reviewed papers from the International Conference on Engineering Tribology Technology 2014 (ICETT 2014), November 21-23, 2014, Nantou, Taiwan.
Structural, Electrical, and Resistance Force Characteristics of Ga-In-Sn Eutectic Alloys.
Keywords: Tribology -- Congresses.; Tribology -- Industrial applications -- Congresses.; Friction -- Analysis -- Congresses.; Surfaces (Technology) -- Analysis -- Congresses.; elektronické knihy; electronic books